Sequential encoding aids working memory for meaningful objects' identities but not for their colors. - Chung, Yong Hoon; Brady, Timothy F.; Störmer, Viola S. (Memory & Cognition, 2024)
Previous studies have found that real-world objects' identities are better remembered than simple features like colored circles, and this effect is particularly pronounced when these stimuli are encoded one by one in a serial, item-based way. Recent work has also demonstrated that memory for simple features like color is improved if these colors are part of real-world objects, suggesting that meaningful objects can serve as a robust memory scaffold for their associated low-level features. However, it is unclear whether the improved color memory that arises from the colors appearing on real-world objects is affected by encoding format, in particular whether items are encoded sequentially or simultaneously. We test this using randomly colored silhouettes of recognizable versus unrecognizable scrambled objects that offer a uniquely controlled set of stimuli to test color working memory of meaningful versus non-meaningful objects. Participants were presented with four stimuli (silhouettes of objects or scrambled shapes) simultaneously or sequentially. After a short delay, they reported either which colors or which shapes they saw in a two-alternative forced-choice task. We replicated previous findings that meaningful stimuli boost working memory performance for colors (Exp. 1). We found that when participants remembered the colors (Exp. 2) there was no difference in performance across the two encoding formats. However, when participants remembered the shapes and thus identity of the objects (Exp. 3), sequential presentation resulted in better performance than simultaneous presentation. Overall, these results show that different encoding formats can flexibly impact visual working memory depending on what the memory-relevant feature is.